Non-communicable Disease Risk Reduction Teaching in India: A Curricular Landscape - Pati, Sanghamitra; Sinha, Rajeshwari; Mahapatra, Pranab (Frontiers in Public Health, 2019)
Non-communicable diseases (NCDs) have today become a growing epidemic, surpassing infectious diseases and adversely impacting national health systems, policies, and socio-economic developments. Management of NCD and its risk factors such as tobacco use, poor diet, physical inactivity, and obesity has garnered paramount importance under the Sustainable Development Goals (SDGs). However, the educational settings for healthcare professionals to prepare them for delivery of preventive interventions w.r.t. to NCD risk factors require a stronger foundation. In the present work, a landscaping exercise of the teaching of NCD risk factors in the extant Bachelor of Medicine and Bachelor of Surgery (MBBS) curricula of healthcare professionals from select medical colleges in India has been undertaken. Our assessment indicates that in the present MBBS curriculum, effort is largely directed upon teaching only specific aspects of NCDs, such as hypertension, diabetes, mental illness, blindness, and cancer with greater inclination toward clinical aspects. With regard to NCD risk factors, there is inadequate focus on the healthcare promotion aspects. The overall syllabus also does not address long-term health implications of tobacco smoking, lack of proper diet or physical activity, excessive alcohol consumption etc. It also does not reflect any practical trainings or sessions related to health promotion or behavior change activities. As a way forward, we suggest that NCD risk reduction aspects be incorporated extensively into existing health professional education through the development of a curricular framework and an intervention plan contextualized to India. Findings from this study are expected to help provide critical inputs for the design and development of a curricular plan with thrust on tobacco cessation, physical activity, healthy diet, and restricted alcohol consumption, leading to creation of a health competent workforce engaged in NCD prevention and health promotion.